PEMANTAUAN EKOLOGI SARANG ELANG JAWA (Spizaets bartelsi) DI WILAYAH HUTAN CIKANIKI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Ridwan, Iwan; AT, Mulyadi; Rusli, Abdul Rahman (Jurnal Nusa Sylva, 2014)
Javanese eagle (Spizaetus bartelsi) is one type of bird of prey endemic to Java. The existence of birds of prey in an ecosystem is very important, because of its position as the top predators in the food chain or pyramid. The purpose of this study was to determine the characteristics and ecological nests, as well as the proliferation of Java Eagle Cikaniki especially in forest areas. Observation method used is cooperative mehod five observation points around forest areas Cikaniki. Through monthly observation, ranges Javanese eagle depicted on the map, and mapped point is the assumption of Javanese eagle nesting sites. Observations are also done through direct observation at the location around the nest. The results explain that Java Eagle identified seven individuals that belong to three families: Pengkeh family, relatives and family Andam I Andam II. During the observation, observed breeding success of one family, it is characterized by the presence of individual chicks that fly around the nest site. During the monitoring also the sound of Javanese eagle chicks in the vicinity of the nest. Cikaniki in forest areas, family observed using the Java Eagle Castanopsis argentea tree to lay a nest. The tree is a towering trees compared to other tree with a height of about 30 meters. Java Eagle nest situated at an altitude 16 meters above the ground on the second branch. Nest trees grow at an altitude of 1,100 meters above sea level and on a fairly steep slope topography, close to the creeks and within 500 meters of open wilayan limit.